A polydnavirus-encoded ANK protein has a negative impact on steroidogenesis and development. (April 2018) - Ignesti, Marilena; Ferrara, Rosalba; Romani, Patrizia; Valzania, Luca; Serafini, Giulia; Pennacchio, Francesco; Cavaliere, Valeria; Gargiulo, Giuseppe
Abstract: Polydnaviruses (PDV) are viral symbionts associated with ichneumonid and braconid wasps parasitizing moth larvae, which are able to disrupt the host immune response and development, as well as a number of other physiological pathways. The immunosuppressive role of PDV has been more intensely investigated, while very little is known about the PDV-encoded factors disrupting host development. Here we address this research issue by further expanding the functional analysis of ankyrin genes encoded by the bracovirus associated with Toxoneuron nigriceps (Hymenoptera, Braconidae). In a previous study, using Drosophila melanogaster as experimental model system, we demonstrated the negative impact of TnBVank1 impairing the ecdysone biosynthesis by altering endocytic traffic in prothoracic gland cells. With a similar approach here we demonstrate that another member of the viral ank gene family, TnBVank3, does also contribute to the disruption of ecdysone biosynthesis, but with a completely different mechanism. We show that its expression in Drosophila prothoracic gland (PG) blocks the larval-pupal transition by impairing the expression of steroidogenic genes. Furthermore, we found that TnBVank3 affects the expression of genes involved in the insulin/TOR signaling and the constitutive activation of the insulin pathway in the PG rescues the pupariation impairment. Collectively, our data demonstrate that Tn BVANK3 acts as a virulence factor by exerting a synergistic and non-overlapping function with Tn BVANK1 to disrupt the ecdysone biosynthesis. Graphical abstract: Highligths: Expression of TnBVank3 in Drosophila prothoracic gland blocks pupariation. TnBVank3 negatively affects the expression of the insulin/TOR signaling components. TnBVank3 down-regulates genes of the ecdysone biosynthetic pathway.